the Manajemen Kerja Tim (Team Work) dalam Pendidikan Islam - Febrina, Winda; Jamilus, Jamilus (Komunitas Manajemen Kompetitif, 2024)
Islamic education has an important role in shaping the character and noble character of the younger generation. To achieve this goal, effective and efficient teamwork management is needed in the learning and coaching process. Teamwork management is an important aspect in the success of an organization. An effective team can increase productivity, creativity and innovation. This paper discusses teamwork management in Islamic education, including the basics of the Qur'an and Sunnah, the principles of teamwork management, and strategies for its application in education.